COVID-19 and Forests in Canada and the United States: Initial Assessment and Beyond - Stanturf, John A.; Mansuy, Nicolas (Frontiers in Forests and Global Change, 2021)
Information on the effects of a novel coronavirus, COVID-19, on forests in Canada and the United States was derived from existing published studies and reports, news items, and policy briefs, amplified by information from interviews with key informants. Actions taken by governments and individuals to control the spread of the virus and mitigate economic impacts caused short-term disruptions in forest products supply chains and accelerated recent trends in consumer behavior. The COVID-19 containment measures delayed or postponed forest management and research; a surge in visitation of forests near urban areas increased vandalism, garbage accumulation, and the danger of fire ignitions. Forests and parks in remote rural areas experienced lower use, particularly those favored by international visitors, negatively affected nearby communities dependent upon tourism. Physical distancing and isolation increased on-line shopping, remote working and learning; rather than emerging as novel drivers of change, these actions largely accelerated existing trends. On-line shopping sales had an immediate positive effect on the packaging sector and remote working had a significant negative effect on graphic paper manufacturing. More time at home and low interest rates increased home construction and remodeling, causing historically high lumber prices and localized material shortages. The response to the pandemic has shown that rapid social change is possible; COVID-19 presents a once in-a-lifetime opportunity to shift the global development paradigm towards greater sustainability and a greener, more inclusive economy, in which forests can play a key role. In both Canada and the United States, the notion of directing stimulus and recovery spending beyond meeting immediate needs, towards targeting infrastructure development, has momentum.